La philosophie comme législation axiologique Platon nietzschéen? - Wotling, Patrick (Estudios Nietzsche, 2024)
In Nietzsche’s view, Plato certainly is not just any philosopher. First and foremost because of what Nietzsche refers to as his particular « sphinx nature » (BGE, § 28), his insuperable and artistic « secrecy » (BGE, § 28), his ability to hide, and sometimes even to lie : which means that it is extremely difficult to ascribe to him any precise, indisputable philosophical position, doctrine or notion. As is apparent, Nietzsche’s Plato is therefore completely different from the character usually discussed by other philosophers. Why then, is he so intensely interested in Plato if he does not take his so-called major theories seriously ? A closer scrutiny of Nietzsche’s corpus reveals that there is something really specific about Plato : his deep, mostly hidden, and sharp-sighted understanding of philosophy (and philosophers) ; namely not as a theoretical search for knowledge and truth, but as practical value creation and legislation, in other words as an activity intent on carving a new type of human life and being, very much akin to Nietzsche’s own analysis.